2019
DOI: 10.1002/jcb.29135
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor gene polymorphism is associated with multiple myeloma

Abstract: Objectives The aim of this study was to explore the Vitamin D receptor (VDR) gene polymorphism and its association with multiple myeloma (MM) development. Methods The peripheral blood of 40 MM cases and 84 healthy controls were collected. Polymerase chain reaction (PCR) and DNA sequencing were applied to detect VDR gene polymorphism (including: FokI, BsmI, ApaI, and TaqI). SHESIS biological information software was used to analyze genotypes, alleles, linkage disequilibrium (LD), haplotype distribution, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Further analysis revealed that amplification of 1q21 with 4 or more copies served as a prognostic factor for adverse events in MM and 1q21 gains even predicted a poor overall survival in patients receiving Bortezomib-based treatment regimens. Finally, Vitamin D receptor gene polymorphisms, TaqI (C allele) and BsmI (A allele) had higher frequency and increased risk of MM in Chinese MM patients ( n =40, ethnicity not known) [89] .…”
Section: Studies In Brazilian Populationmentioning
confidence: 91%
See 1 more Smart Citation
“…Further analysis revealed that amplification of 1q21 with 4 or more copies served as a prognostic factor for adverse events in MM and 1q21 gains even predicted a poor overall survival in patients receiving Bortezomib-based treatment regimens. Finally, Vitamin D receptor gene polymorphisms, TaqI (C allele) and BsmI (A allele) had higher frequency and increased risk of MM in Chinese MM patients ( n =40, ethnicity not known) [89] .…”
Section: Studies In Brazilian Populationmentioning
confidence: 91%
“… Russian 69 IL-6 CC genotype ( [81] 12. Chinese 67 CCND1 G870A (GG variant) [82] ) 129 MDR1 C1236T (CC genotype C3435T (CC genotype) [84] ) 827 NCOA1 HLA-I rs79480871 rs6457327 ( [86] 40 VDR TaqI (C allele) BsmI (A allele) [89] ) 13. Korean 196 MTHFR 677CC 1298CC [90] 117 NQO1 NQO1*2/*2 genotype [92] 14.…”
Section: Population Pharmacogenetics Of MMmentioning
confidence: 99%
“…Vitamin D: Even in the case of MM, there seems to be a relationship between this hormone and the probability of the onset of the disease: patients with MM have a greater deficiency of vitamin D and this deficiency appears “alarming” in patients with bone lesions [ 101 ]. Specific polymorphisms of the vitamin D receptor (VDR) gene are associated with MM and may be a molecular marker of risk [ 102 ].…”
Section: Lymphoid Malignanciesmentioning
confidence: 99%
“…VRD polymorphisms have been reported in MM cell lines with an increased risk stage. Specifically, single-nucleotide polymorphisms (SNPs) within vascular endothelial growth factor (VEGF) and VDR (Fok1) have been reported in several studies [ 121 , 122 , 123 , 124 ]. These reports were confirmed by a different group of researchers, who studied plasmablastic lymphoma and myeloma cells more broadly [ 120 ].…”
Section: Vitamin D Status In Multiple Myelomamentioning
confidence: 99%